Character Based Module Development for the Practicality of Social Science Learning Process in Elementary School - Saqjuddin S; Muhammad Nawir; Idawati i (Indonesian Journal of Primary Education, 2021)
The development of character based modules for the practicality of the elementary social studies learning process is part of the efforts made to overcome learning problems. Facts obtained in the field, the learning process is directed at children's ability to memorize information without understanding the information obtained, so that the impact is unable to develop children's ability to think critically and systematically. The purpose of this research is to develop a character-based module for the elementary social studies learning process. This type of research and development uses a 4-D (Four-D) development model which consists of four stages, namely the definition stage, the design stage, the development stage, and the dissemination stage. The practicality test is carried out after the development stage. The data collection technique in this study was using a questionnaire, namely a teacher response questionnaire and a student response questionnaire. Data validation was carried out by 2 validators, namely expert validators in the field of social science and practitioner validators. Practical analysis uses the results of teacher and student responses. The module is said to be practical if it is at a fairly practical level, which is at number 3 out of 4 (very practical). The results of the analysis, the character-based module which is stated to be very practical, can be seen from the results of the teacher's response questionnaire and the student's response with an overall average score of 4 very practical, thus providing the development and application of the character-based module very practical because it can make it easier for teachers and students. learn in the learning process.